The Role of Kaili Tara Culture Based on Habits in Character Formation of Early Childhood at State Kindergarten 2, Parigi Tengah - Nurafni Lamanje; Nurhayati Nurhayati; Sita Awalunisah (FKIP - Universitas Riau, 2026)
The problem in this study lies in the character values of children who have not developed well. This study aims to analyze whether there is a role of Kaili Tara culture in the formation of early childhood character using qualitative methods. The population in this study were all students in group B of Tk Negeri 2 Parigi Tengah, totaling 15 children. The collection technique was carried out through observation, documentation, interviews and assessment rubrics. The aspects observed in this study were aspects of politeness, aspects of responsibility and aspects of obedience to regulations. Researchers can draw the conclusion that there is a role of Kaili Tara culture in the formation of children's character in Tk Negeri 2 Parigi Tengah through the habituation method. This can be proven by the following observation results: the results of the recapitulation of the role of Kaili Tara culture in the formation of children's character from all aspects before the implementation of habituation activities were 11% in the category (BSB), 16% in the category (BSH), 29% Starting to Develop (MB) and 44% in the category (BB). and it can be seen that the results of the recapitulation of the role of Kaili Tara culture in the formation of children's character from all aspects in the fourth week are 25% in the Very Well Developed (BSB) category, 45% in the Developed According to Expectations (BSH) category, 20% Starting to Develop (MB) and 10% in the Not Yet Developed (BB) category.